If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6n + -1 = 18 Reorder the terms: 1 + -1 + -6n = 18 Combine like terms: 1 + -1 = 0 0 + -6n = 18 -6n = 18 Solving -6n = 18 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-6'. n = -3 Simplifying n = -3
| 4y+2+6y-50=180 | | 3(-2x+1)-5=10 | | -2p+3=p+9 | | .5y-3=2y+12 | | s+6=4 | | -6=6x-6+x | | -(y-3)=2y+6 | | 4.50+0.05=0.20x-4.50 | | 4=-8.0n | | x+(26+x)=64 | | 5w^2+12w^2= | | 8(y-1)=3y+17 | | -5k-2k=14 | | -4-9/3=-7 | | -7(n+3)=-34+6n | | 64x^2-192x=0 | | 4.7=30 | | .4*-.03= | | 7x+22=11x+68 | | V-39=-17 | | 3=k+4+5 | | 21x+3=12x+6 | | -(1-7x)=4x-13 | | 2x^2-12x-27=0 | | 5=5-4s-7s | | .4x-.03= | | 3x+x+40=180 | | x-20+2-(-7)=9 | | 3b-5+6b=-5 | | 1/6X-5=-11 | | 11-(8-8n)=8 | | (-16)-(-t)=(-45) |